Implementation of the Jigsaw Model Assisted by E-Modules in Science Learning on Ecosystem Material for Class V Elementary Schools - Tri Susilowati; Bambang Ismanto; Widiasih (Jurnal Penelitian Pendidikan IPA, 2023)
Critical thinking skills, independence, and low learning outcomes for most students are the essential background for this research. This problem causes the learning process carried out in class not to run optimally. This research aims to determine the influence of implementing the Jigsaw learning model assisted by e-modules on students' critical thinking abilities, independence, and learning outcomes. The approach in this research is quantitative with a Quasi-Experimental research type. The design of this research is Posttest Control Group Design. The population is classes VA and VB using total sampling techniques where all population members are used as research samples. Data collection techniques include questionnaires (measuring critical thinking abilities and learning independence) and tests to measure learning outcomes. The analysis shows the influence of using the Jigsaw-type cooperative learning model assisted by e-modules on critical thinking skills, independence, and student learning outcomes in grade 5 elementary school ecosystem material. Thus, learning with the Jigsaw model can overcome students' learning problems and needs.